2019
DOI: 10.5194/acp-19-8101-2019
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of snowfall over Greenland from CloudSat observations

Abstract: Abstract. We use the CloudSat 2006–2016 data record to estimate snowfall over the Greenland Ice Sheet (GrIS). We first evaluate CloudSat snowfall retrievals with respect to remaining ground-clutter issues. Comparing CloudSat observations to the GrIS topography (obtained from airborne altimetry measurements during IceBridge) we find that at the edges of the GrIS spurious high-snowfall retrievals caused by ground clutter occasionally affect the operational snowfall product. After correcting for this effect, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 34 publications
12
58
0
Order By: Relevance
“…Since the reanalyses routinely assimilate water vapor from satellite observations, this integrated accumulation is well constrained by independent satellite observations and provides a strong constraint on the net snowfall over the ice sheet. This result is further supported by Boening et al (2012), who show remarkable consistency between estimates of recent Antarctic snowfall variability derived from reanalyses and CloudSat and completely independent ice sheet mass estimates from the Gravity Recovery and Climate Explorer (GRACE) satellite.…”
Section: Cloudsat Snowfall Retrievalssupporting
confidence: 62%
“…Since the reanalyses routinely assimilate water vapor from satellite observations, this integrated accumulation is well constrained by independent satellite observations and provides a strong constraint on the net snowfall over the ice sheet. This result is further supported by Boening et al (2012), who show remarkable consistency between estimates of recent Antarctic snowfall variability derived from reanalyses and CloudSat and completely independent ice sheet mass estimates from the Gravity Recovery and Climate Explorer (GRACE) satellite.…”
Section: Cloudsat Snowfall Retrievalssupporting
confidence: 62%
“…The impact of ground-based versus space-borne effective hmin (typically ~0.3 and ~1.2 km, respectively) on surface precipitation occurrence was estimated at both sites to be roughly ±10 percentage points, suggesting hydrometeor nucleation, growth, evaporation, or sublimation within this "blind zone" (not shown; cf. Bennartz et al, 2019;Castellani et al, 2015;Maahn et al, 2014). We note that the impact of the blind zone between the surface and ground-based hmin on precipitation occurrence using high radar sensitivities, similar to those used here, is absent from the literature to our knowledge and merits a dedicated study.…”
Section: Methodsmentioning
confidence: 73%
“…However, other studies have indicated 30-40% spaceborne radar overestimates compared to ground measurements, with results strongly geographically and latitudinally dependent [9]. Additionally, the presence of orography adversely impacts both ground and space-based radars, resulting in underestimation biases >70% [25,26]. In situ ground-based observations of snowfall accumulation also suffer from relatively large uncertainties, as intercomparisons have shown that gauges are biased low, with as much as 50% of the accumulation missed when unshielded and 12-27% with a single perimeter fence [27][28][29].…”
Section: Introductionmentioning
confidence: 93%